Protective Effects of Appropriate Amount of Nuts Intake on Childhood Blood Pressure Level: A Cross-Sectional Study - Feng, Ye; Bi, Yang; Tang, Xian; Zhang, Ping; Tong, Jishuang; Peng, Xin; Tian, Jie; Liang, Xiaohua (Frontiers in Medicine, 2022)
Objective: Increased blood pressure (BP) is a major risk factor to cardiovascular disease in adults. Regular nuts consumption may improve some BP in adults whereas evidence in children are relative lacking. This study aimed to determine the efficacy of nuts intake on BP in children. Methods: Stratified cluster sampling was performed to include a total of 15,268 primary school children aged 6-12 years in urban and rural areas in Southwest China. The daily nuts intake dosage was collected by questionnaires, and generalized linear model (GLM) and logistic regression were used to analyze the relationship between nuts intake and BP. Results: For the total subjects, 11,130 (72.9%) participants consumed < 35 g/d of nuts, 1145 (7.5%) participants consumed 35 g/d ≤ nut < 50 g/d of nuts, 2053 (13.4%) participants consumed 50 100 g/d of nuts and 940 (6.2%) participants consumed over 100 g/d of nut. For sex subgroup, 1074 (13.53%) boys and 979 (13.35%) girls consumed 50 100 g/d of nuts. Compared with 50 100 g/d of nuts intake group, systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were significant differences in < 35 g/d, 35 g/d ≤ nut < 50 g/d, and > 100 g/d nuts intake groups (all P < 0.001). The logistic regression showed that compared with the 50 100 g/d group, the other three groups are more likely associated with childhood hypertension (all P < 0.001). Therefore, a U style relationship between nuts intake and BP level was identified. Conclusions: The finding suggests that intake 50 100 g/d is the recommended dose of nuts intake to control childhood hypertension, as well as for cardio protection purpose.